Scenarios for autoimmunization of T and B cells in myasthenia gravis. - Shiono, H; Roxanis, I; Zhang, W; Sims, G; Meager, A; Jacobson, L; Liu, J; Matthews, I; Wong, Y; Bonifati, M; Micklem, K; Stott, D; et al. (2003)
We have studied responses in thymoma patients to interferon-alpha and to the acetylcholine receptor (AChR) in early-onset myasthenia gravis (EOMG), seeking clues to autoimmunizing mechanisms. Our new evidence implicates a two-step process: (step 1) professional antigen-presenting cells and thymic epithelial cells prime AChR-specific T cells; then (step 2) thymic myoid cells subsequently provoke germinal center formation in EOMG. Our unifying hypothesis proposes that AChR epitopes expressed by neoplastic or hyperplastic thymic epithelial cells aberrantly prime helper T cells, whether generated locally or infiltrating from the circulation. These helper T cells then induce antibody responses against linear epitopes that cross-react with whole AChR and attack myoid cells in the EOMG thymus. The resulting antigen-antibody complexes and the recruitment of professional antigen-presenting cells increase the exposure of thymic cells to the infiltrates and provoke local germinal center formation and determinant spreading. Both these and the consequently enhanced heterogeneity and pathogenicity of the autoantibodies should be minimized by early thymectomy.